Ossicular status in patients operated for chronic suppurative otitis media - Monika Sharma; Devi Prasad Shetty (International Journal of Medical Research and Review, 2016)
Introduction: Chronic suppurative otitis media (CSOM) is a chronic inflammation of the middle ear and mastoid cavity, which presents with recurrent ear discharge through a tympanic perforation. The WHO has classified India as a country with highest prevalence ( > 4%) requiring urgent attention to deal with a massive public health problem. CSOM is often associated with a bone eroding process which occurs due to the presence of cholesteotoma, granulation tissue or both.Methods: This study was conducted in a department of E.N.T, Yenepoya Medical College Hospital, Deralakatte, Mangalore for a period of 2 years. This study was conducted to evaluate the ossicular involvement in chronic suppurative otitis media (CSOM). A retrospective-prospective study was conducted over a 2-year period on 86 patients who underwent surgery for the disease. Demography, ossicular status and hearing loss were studied and analyzed using SPSS programme.Results: The study revealed Tubotympanic disease was the more common type of disease. Ossicular necrosis was present in 35% of population. The most common ossicles involved were the whole of incus, followed by lenticular process and long process of incus. There was a higher incidence of ossicular disruption in atticoantral disease than in tubotympanic disease.